Symptomatic congenital syphilis in a tertiary neonatal unit: a retrospective descriptive study - Pillay, Shakti (Division of Neonatology, 2017)
Background: Syphilis is a disease that was first described in the 1300s and now 700 years later, despite preventive measures and effective treatment, continues to impact on a global scale, with the burden falling largely on the developing world. We could find no recent published literature looking at predictors of outcomes in neonates born with symptomatic congenital syphilis, especially in the context of a tertiary neonatal setting. Methodology: The study design was a retrospective descriptive folder review of neonates born with symptomatic congenital syphilis at Groote Schuur Hospital (GSH) from January 2011 to December 2013. One of the primary objectives was to address outcome as well as look at modifiable preventable factors. All neonates treated at GSH (inborn and outborn) who tested serologically positive for syphilis together with clinical signs of syphilis were included. Data was obtained from the National Health Laboratory System (NHLS) database, as well as the notification and death registers at GSH nursery. All data was collected in a Microsoft excel spread sheet and analysed using Microsoft StatPlus. Results: Fifty of eighty neonates (62.5%) with positive syphilis serology as well as clinical signs of congenital syphilis were included together with their fifty mothers. The majority (98%) of mothers were inadequately untreated. Nineteen neonates demised. There were no statistically significant differences between the deaths and survivors in terms of gestational age (p = 0.15), birth weight (p = 0.08) or maternal age (p = 0.51). Two significant predictors of mortality were one minute and five minute Apgar scores of less than five ([RR], 3.5; 95% CI 1.6-7.7 and [RR], 2.9; 95% CI 1.5-5.3 respectively). Hydropic neonates, tended to be sicker at birth, requiring intubation and inotropes, which was associated with a poorer outcome (increased risk of mortality). Conclusion: Despite the introduction of a National Syphilis Screening programme more than twenty years ago together with a large proportion of pregnant women having access to antenatal care, congenital syphilis is still prevalent in South Africa. Failure to access antenatal care, poor partner tracing and a number of modifiable health worker related failures contribute to poor maternal diagnosis and treatment. Many neonates with congenital syphilis require aggressive interventions and there is a high mortality rate. This dissertation adds to the existing body of research particularly with regard to predictors of outcome in tertiary neonatal settings. Certain categories of neonates have a lower survival rate and guidelines about limitation of care may need to be considered in order to optimise resource allocation particularly in resource-constrained settings. Further research is required to elaborate how best to develop protocols in these neonates.